Mengintegrasikan Iman dan Bisnis: Praktik Theopreneurship dari Kisah Ishak di Kejadian 26:1-33 - Panjaitan, Tutur Parade Tua; Setiawan, Irwan (STT Internasional Harvest Tangerang, 2025)
In the ever-evolving global dynamics, entrepreneurship plays an important role in driving economic growth and offering solutions to complex problems. However, the entrepreneurial paradigm generally still focuses on market logic and traditional business strategies, while the spiritual and theological aspects are often overlooked. The purpose of this research is to analyze the concept of theopreneurship, entrepreneurship based on faith, through Isaac's narrative in Genesis 26:1-33. This story shows how Isaac faced economic and social challenges in Gerar, including conflict, famine, and interactions with the locals, while remaining obedient to God's direction. The analysis uses the method of exegesis with a practical theological approach, to trace the principles of Christian faith-based business embodied in the narrative. The results of the study show that Isaac's success was not solely the result of human strategy, but a combination of obedience to God, diplomacy and harmonious social relations, as well as a strategy of growth and sustainability. These findings provide an applicative framework for modern entrepreneurs to integrate business faith and strategy, prioritize integrity and ethics, and manage resources wisely in the practice of theopreneurship.